2023
DOI: 10.32829/ghmj.v7i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Nursing training: Self-care in patients undergoing hematopoietic stem cell transplantation in a specialized oncologic institution [Entrenamiento enfermería: Autocuidado en pacientes sometidos a trasplante de progenitores hematopoyéticos en una institución especializada oncológica]

Abstract: Self-care in post-transplanted patients of hematopoietic progenitors at home is transcendental to improve their health conditions. The purpose of the educational activity on self-care is to establish communicative strategies to improve their situation, reducing preventable post-transplant complications and avoiding constant readmissions. The personalized counseling provided by the nurse to the patient and family members improves their quality of life. Objectives: To determine the level of self-care of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In relation to the dimensions: knowledge 94.4%, skills 87% presented high levels respectively. It is concluded that continuing nursing education maintains solvency in self-care in the patient's daily life (Huamán et al, 2023).…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…In relation to the dimensions: knowledge 94.4%, skills 87% presented high levels respectively. It is concluded that continuing nursing education maintains solvency in self-care in the patient's daily life (Huamán et al, 2023).…”
Section: Bibliographic Reviewmentioning
confidence: 99%